The influence of digital development on China’s carbon emission efficiency: In the view of economic and environmental balance - Ding, Yuan; Yang, Yalan (Frontiers in Environmental Science, 2023)
With the worsening global climate problem, carbon peak and carbon neutrality has become a crucial object to realize sustainable development. Regarded as the engine of economic development in the new era, it is worth exploring whether digitalization could contribute to carbon goals. However, carbon reduction at the cost of economic recession should not be advocated and contains the risk of reversal when economy renews in growth. Therefore, by using the total factor NDDF model, this paper evaluates carbon efficiency which reflects economic performance and environmental performance of 246 China’s prefecture level cities during the period of 2011 to 2019. A fixed effect model and mediation effect models are used to explore the non-liner relationship and transmission channels between digital development and carbon efficiency. It is found that: (1) digital development would hinder carbon efficiency first, and then turns to promoting it after reaching a certain level; (2) digital development could indirectly affect carbon efficiency through industrial agglomeration, industrial structure upgrading, and industrial electricity productivity also in non-liner ways. (3) Heterogeneity exists in the relationship between digital development and carbon efficiency due to different regions and development types.